Pengaruh Gaya Kepemimpinan Partisipatif Terhadap Implementasi Kurikulum Merdeka di Madrasah - Riska; Nurmayuli (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2025)
The change in the national curriculum policy from the 2013 Curriculum to the Merdeka Curriculum requires readiness and strategic adaptation from educational units, particularly in the aspect of leadership. The participatory leadership style is considered relevant in supporting the successful implementation of this curriculum because it emphasizes collaboration, teacher involvement, and joint decision-making. This research aims to analyze the effectiveness of the participatory leadership style of the head of the madrasa and to examine its influence on the implementation of the Merdeka Curriculum at Madrasah Aliyah Ruhul Islam Anak Bangsa (RIAB) Aceh Besar. The research method employs a quantitative approach with survey techniques through Likert questionnaires to 27 respondents consisting of teachers and madrasah principals. The research instrument has been tested for validity and reliability and is deemed suitable. The results of descriptive analysis show that the participative leadership style is categorized as "Effective" (80.2%), while the implementation of the Merdeka Curriculum is classified as "Fairly Effective" (78.7%). However, the results of simple linear regression testing indicate that the participative leadership style does not have a significant effect on curriculum implementation (t hitung 2.009 < t tabel 2.060; p > 0.05). These findings suggest that there are other more dominant factors in determining the success of the Merdeka Curriculum implementation in madrasah